Loss of Vancomycin-Resistant Enterococcus Fecal Dominance in an Organ Transplant Patient With Clostridium difficile Colitis After Fecal Microbiota Transplant. (3rd June 2015) - Stripling, Joshua; Kumar, Ranjit; Baddley, John W.; Nellore, Anoma; Dixon, Paula; Howard, Donna; Ptacek, Travis; Lefkowitz, Elliot J.; Tallaj, Jose A.; Benjamin, William H.; Morrow, Casey D.; Rodriguez, J. Martin
Abstract : We report the use of fecal microbiota transplantation in a single heart-kidney transplant recipient with recurrent Clostridium difficile, vancomycin-resistant Enterococcus (VRE) fecal dominance, and recurrent VRE infections. Fecal microbiota transplantation resulted in the reconstruction of a diverse microbiota with (1) reduced relative abundance of C difficile and VRE and (2) positive clinical outcome.